Nanogels as novel drug nanocarriers for CNS drug delivery - Manimaran, V.; Nivetha, R. P.; Tamilanban, T.; Narayanan, J.; Vetriselvan, Subramaniyan; Fuloria, Neeraj Kumar; Chinni, Suresh V.; Sekar, Mahendran; Fuloria, Shivkanya; Wong, Ling Shing; Biswas, Anupam; Ramachawolran, Gobinath; et al. (Frontiers in Molecular Biosciences, 2023)
Nanogels are highly recognized as adaptable drug delivery systems that significantly contribute to improving various therapies and diagnostic examinations for different diseases. These threedimensional, hydrophilic cross-linked polymers have the ability to absorb large amounts of water or biological fluids. Due to the growing demand for enhancing current therapies, nanogels have emerged as the next-generation drug delivery system. They effectively address the limitations of conventional drug therapy, such as poor stability, large particle size, and low drug loading efficiency. Nanogels find extensive use in the controlled delivery of therapeutic agents, reducing adverse drug effects and enabling lower therapeutic doses while maintaining enhanced efficacy and patient compliance. They are considered an innovative drug delivery system that highlights the shortcomings of traditional methods. This article covers several topics, including the involvement of nanogels in the nanomedicine sector, their advantages and limitations, ideal properties like biocompatibility, biodegradability, drug loading capacity, particle size, permeability, non-immunological response, and colloidal stability. Additionally, it provides information on nanogel classification, synthesis, drug release mechanisms, and various biological applications. The article also discusses barriers associated with brain targeting and the progress of nanogels as nanocarriers for delivering therapeutic agents to the central nervous system.